2012
DOI: 10.1007/s13225-011-0149-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of Trametes and related genera, and description of a new genus Leiotrametes

Abstract: A phylogenetic analysis of Trametes and related taxa is proposed, based on a wide sampling of temperate and tropical species. Concatenate sequences of ribosomal DNA (ITS1-5.8S-ITS2) and RPB2 gene from mycelia cultures were analyzed by Maximum Likelihood and Bayesian methods, whilst morphological features were documented from the corresponding herbarium vouchers. Congruent results were obtained from analyses of ribosomal LSU sequences downloaded from Genbank. The Bayesian analysis of ITS + RPB2 sequences gave t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 27 publications
1
33
1
Order By: Relevance
“…material 2). Thus, contrary to the uncertain position of T. cingulata within the genus Trametes (Welti et al 2012), our results revealed that the latter does not belong to Trametes sensu stricto in the sense of Justo and Hibbett (2011) and Welti et al (2012) (Fig. 3; Suppl.…”
Section: Phylogenetic Positions Of Trametes Species Of Benincontrasting
confidence: 95%
See 2 more Smart Citations
“…material 2). Thus, contrary to the uncertain position of T. cingulata within the genus Trametes (Welti et al 2012), our results revealed that the latter does not belong to Trametes sensu stricto in the sense of Justo and Hibbett (2011) and Welti et al (2012) (Fig. 3; Suppl.…”
Section: Phylogenetic Positions Of Trametes Species Of Benincontrasting
confidence: 95%
“…clustered together with T. flavida with high support in the ITS dataset (PP = 0.84/BS = 89) and the combined ITS-LSU datasets (PP = 0.98/BS = 99). Both species share also high morphological similarity (Welti et al 2012; Fig. 2C, D) and a tropical distribution.…”
Section: Phylogenetic Positions Of Trametes Species Of Beninmentioning
confidence: 82%
See 1 more Smart Citation
“…1. This species was formerly named as Coriolopsis polyzona, but recently, it was included in the Trametes genus (Justo and Hibbett 2011;Welti et al 2012). Therefore, due to the high degree of similarity, we have named this strain as T. polyzona LMB-TM5 (GenBank accession number KP835541).…”
Section: Molecular Identificationmentioning
confidence: 99%
“…Although the sequence obtained from the Neolithic polypore was identical to both sequences of D. confragosa and D. tricolor, they classified it as D. tricolor because of the lamellate hymenophore. In other studies dealing with the molecular phylogeny of the Polyporales this obvious ambiguity was overcome by using only one of the species in the alignment (Hibbett & Donoghue 1995, Justo & Hibbett 2011, Welti et al 2012.…”
Section: Introductionmentioning
confidence: 99%